Role of psychophysiological state in competitive activity of team athletes - Lutkova, N. V.; Makarov, Yu. M.; Minkin, V. A.; Nikolaenko, J. N.; Egorenko, L A. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to determine a differentiated impact of psychophysiological parameters of team athletes on their competitive activity as well as determine the possible combination of these parameters that would ensure stable competitive results.